The Egyptian Private-Climate Nexus: Private Sector Perceptions on the Green Transition - Shaheen, Yehia (AUC Knowledge Fountain, 2023)
The issue of climate change poses the most pressing threat for humanity. This is especially the case amongst developing countries who, while emitting the minority of global emissions, are forecast to bear the most damage. Such is the case with Egypt, who suffers from marked water scarcity and is vulnerable to climate change driven detriments across a number of levels. As climate finance and private sector investments are key towards the green transition; transitioning to a green economy to fight the adverse impacts of climate change, this thesis aims to analyze the perceptions of private sector actors on the issue of the green transition within the Egyptian context. Through the use of semi-structured interviews within the framework of a qualitative analysis relying on the open-coding approach, perceptions of various private sector actor demographics were recorded; including multinationals, Egyptian private sector firms with clear sustainability mandate/positionalities, as well as Egyptian private sector firms with no sustainability mandates. The interview data identified that while there was a universal recognition of the issue of climate change, not all firms operationalized such an understanding within the scope of their business operations- associating it with key challenges such as cost issues, issues with the existing legal and regulatory framework, macroeconomic uncertainty and concerns, as well as lack of awareness and culture-related issues. The participants identified a number of desired incentives towards catalyzing activity in the potential Egyptian green economy, including fiscal incentives and business facilitations, legal and regulatory reform, as well as further government investment in climate based capacity building and awareness. Despite such concerns, there was an almost unanimous positive outlook on the future of the green economy in Egypt. Towards that end, the study recommends the implementation of a newfound comprehensive legal and regulatory framework to operationalize government strategies for the green economy, improve communication with the private sector, increase investments in awareness and capacity building for the general public and business on climate change issues and the green economy, as well as undertake further partnerships with the private sector and multilateral actors to benefit from global best practices and expertise.